Algoritmos do silêncio: as relações entre o ensino e as aprendizagens de estudantes surdos e professor, em atividades de programação com o Scratch - Silva, Raisson Alves da (2024)
In most cases, deaf children born to hearing parents enter school without proficiency in either Sign Language (Libras) or Portuguese. This study investigates how computer programming with Scratch can contribute to the teaching and learning process of deaf students. Theoretical frameworks were drawn from the works of Paulo Freire, José Carlos Libâneo, Tatiana Bolivar Lebedeff, and Ronice Muller de Quadros. The research conducted during the Professional Master’s Degree in Teaching in Basic Education at the Stricto Sensu Graduate Program of CEPAE/UFG, involved four deaf students from the eighth grade of elementary school at a public school affiliated with the Goiânia Association of the Deaf. Data collection methods included semi-structured interviews in Libras and video recordings of student activities. Approximately 30 hours of recordings were analyzed, revealing changes in students' problem solving strategies and collaborative behavior. The research produced an educational resource for teachers titled "ALGORITHMS OF SILENCE: THE POSSIBILITIES OF SCRATCH FOR DEAF STUDENTS," which outlines all the activities used in data collection and provides suggestions for their implementation. The findings indicate that, like other pedagogical tools, computer programming with Scratch, when used intentionally by teachers, can positively impact the teaching and learning process of deaf students.